Anticipation, teamwork and cognitive load: chasing efficiency during robot-assisted surgery. Issue 2 (8th July 2017) - Sexton, Kevin; Johnson, Amanda; Gotsch, Amanda; Hussein, Ahmed A; Cavuoto, Lora; Guru, Khurshid A
Abstract : Introduction: Robot-assisted surgery (RAS) has changed the traditional operating room (OR), occupying more space with equipment and isolating console surgeons away from the patients and their team. We aimed to evaluate how anticipation of surgical steps and familiarity between team members impacted efficiency. Methods: We analysed recordings (video and audio) of 12 robot-assisted radical prostatectomies. Any requests between surgeon and the team members were documented and classified by personnel, equipment type, mode of communication, level of inconvenience in fulfilling the request and anticipation. Surgical team members completed questionnaires assessing team familiarity and cognitive load (National Aeronautics and Space Administration – Task Load Index). Predictors of team efficiency were assessed using Pearson correlation and stepwise linear regression. Results: 1330 requests were documented, of which 413 (31%) were anticipated. Anticipation correlated negatively with operative time, resulting in overall 8% reduction of OR time. Team familiarity negatively correlated with inconveniences. Anticipation ratio, per cent of requests that were non-verbal and total request duration were significantly correlated with the console surgeons' cognitive load (r=0.77, p=0.006; r=0.63, p=0.04; and r=0.70, p=0.02, respectively). Conclusions: Anticipation and active engagement by the surgical team resulted in shorter operative time, and higher familiarity scores were associated with fewer inconveniences. Less anticipation and non-verbal requests were also associated with lower cognitive load for the console surgeon. Training efforts to increase anticipation and team familiarity can improve team efficiency during RAS.